Salvage lenvatinib/everolimus combination therapy after immune checkpoint inhibitor and VEGFR tyrosine kinase inhibitor for metastatic renal cell carcinoma - Kwok, Christopher; Khorasanchi, Adam; Psutka, Sarah P.; Hinkley, Megan; Dason, Shawn; Sundi, Debasish; Yang, Yuanquan; Yang, Yajing; Verschraegen, Claire; Gross, Evan E.; Orcutt, Delaney; Yin, Ming (Frontiers in Oncology, 2023)
The optimal treatment for metastatic renal cell carcinoma (mRCC) patients who have progressed after both immune checkpoint inhibitor (ICI) and VEGFR tyrosine kinase inhibitor (TKI) remains uncertain. Lenvatinib/Everolimus (LE) is frequently used in combination as salvage therapy, because of their different antitumor mechanisms, but efficacy and toxicity data in this setting are lacking. We retrospectively reviewed charts from two academic centers for 71 adult mRCC patients who received LE after prior ICI and TKI exposure. We evaluated patient demographics, histology, International mRCC Database Consortium (IMDC) risk group, treatment history, and toxicity details. Outcomes of interest included objective response rate (ORR), time to treatment failure (TTF), overall survival (OS), ≥ grade 3 toxicities, and schedule or dosage changes, which were evaluated using descriptive statistics, chi-square test, Cox proportional hazards model and the Kaplan-Meier method. The median age was 64 (range: 31–84). Most patients had clear cell histology (84.5%) and had undergone nephrectomy (80.3%). IMDC risks were favorable (19.7%), intermediate (int) (66.2%), poor (11.3%), and unknown (2.8%). Average ORR was 26.8%, while the median TTF was 5.5 months (95% confidence interval [CI], 3.5–7.6) and median OS was 9 months (95% CI, 7.6-12.9). Intermediate and poor IMDC risks were independently associated with a significantly worse TTF compared to favorable risk (HR, 3.03, 95% CI, 1.18-7.79), as was ≥4L treatment vs. 2L/3L treatment (HR, 2.02, 95% CI, 1.08-3.8). Of the 71 patients, 57.7% had ≥ grade 3 adverse events, 60% had treatment interruption, 44.3% had dose reduction, and 21% stopped treatment due to intolerance. LE therapy is feasible but has modest efficacies following ICI/TKI treatment. Patients with favorable risk or treated earlier may have a better treatment response. These observations need to be confirmed in prospective studies.